Mathematical correlation in the mathematics book for the third intermediate grade in Iraq (Journal of the College of Basic Education, 2022)
The current research aims to identify the mathematical correlation in the mathematics textbook for the third intermediate grade in Iraq.This was done by answering the following question:What is the percentage of mathematical correlation in the mathematics textbook for the third intermediate grade students? The researchers followed the analytical descriptive research method and prepared a questionnaire that represents the criteria of mathematical correlation, which included (linking the components of mathematical knowledge, linking different representations of mathematical concepts, the relationship between mathematical topics, the use of mathematics in other fields, the use of mathematics in daily life, the vision of mathematics as an integrated whole, and the application of thinking and modeling mathematics in solving problems, and appreciating the role of mathematics in culture and society).The researchers used statistical tools (Cronbach's alpha, weighted mean, weight percentile).